Surface Acoustic Wave Sensor for Selective Detection of Flumequine. (2015) - Ktari, N.; Fourati, N.; Zerrouki, C.; Ruan, M.; Nassoko, D.; Seydou, M.; Yaakoubi, N.; Chehimi, M.M.; Kalfat, R.
Abstract: A surface acoustic wave (SAW) sensor functionalized with a thin layer of polypyrrole (PPy) molecularly imprinted polymer (MIP) was designed for the selective detection of flumequine (FLU), a fluoroquinolone antibiotic usually used in intensive aquaculture. Contrarily to previous studies, in which immunosensors were developed to detect low levels of fluoroquinolone, here, the recognition layer does not require any special treatment for stability over a long period of time. The detection limit was of order of 10 -6 M and the sensitivity was estimated at 9.4 ± 0.4°/mM. Selectivity tests, made with levofloxacin, show that the developed sensor displayed an excellent recognition capacity toward flumequine. Quantum chemical calculations, based on the density functional theory (DFT), have permitted to highlight the nature of interactions between the investigated molecular systems and polypyrrole matrix.